POTENSI AIRTANAH PADA BATUAN SEDIMEN VULKANIK DENGAN PENGUKURAN GEOLISTRIK DAERAH KECAMATAN PRAMBANAN, SLEMAN, YOGYAKARTA - Wisnu Aji Dwi Kristanto; Nandra Eko Nugroho; Thamzez Nuur Anom; Ahmad Muhaimin (KURVATEK, 2020)
Abstract Water is a basic human need for life. Increasing the world's population The quality of surface water is increasing, while the air demand will not stop. The source of clean water besides surface water is groundwater. Therefore, using groundwater as a source of air must be further for continuation. Prambanan area with geological conditions compiled by volcanic sedimentary rock available groundwater potential needs to be done related to groundwater in different places depending on where there is no layer containing groundwater. Identification of groundwater potential carried out in the study area using the geoelectric method. The results of geoelectric measurements show subsurface resistivity cross sections of the study area have two aquifer layers with the first layer 2 meters to 10 meters and the second layer 5 meters to 14 meters which are mostly found in lapilli units and some in sandstones and breccias. Keywords: groundwater potential, volcanic sedimentary rocks, geoelectric